Metabolome and RNA-seq Analysis of Responses to Nitrogen Deprivation and Resupply in Tea Plant (Camellia sinensis) Roots - Xu, Wenluan; Li, Jing; Zhang, Luyu; Zhang, Xuyang; Zhao, Hua; Guo, Fei; Wang, Yu; Wang, Pu; Chen, Yuqiong; Ni, Dejiang; Wang, Mingle (Frontiers in Plant Science, 2022)
Nitrogen (N) is an important contributor in regulating plant growth and development as well as secondary metabolites synthesis, so as to promote the formation of tea quality and flavor. Theanine, polyphenols, and caffeine are important secondary metabolites in tea plant. In this study, the responses of C. sinensis roots to nitrogen deprivation and resupply were investigated by metabolome and RNA-seq analysis. Nitrogen deficiency induced content increase for most AAs and reduction for the remaining AAs, polyphenols, and caffeine. After nitrogen recovery, the decreased AAs and polyphenols showed a varying degree of recovery in content, but caffeine did not. Meanwhile, theanine increased in content, but its related synthetic genes were down-regulated, probably due to coordination of the whole nitrogen starvation regulatory network. Flavonoids-related pathways were relatively active following nitrogen stress according to KEGG enrichment analysis. Gene co-expression analysis revealed TCS2, AMT1;1, TAT2, TS, and GOGAT as key genes, and TFs like MYB, bHLH, and NAC were also actively involved in nitrogen stress responses in C. sinensis roots. These findings facilitate the understanding of the molecular mechanism of N regulation in tea roots and provide genetic reference for improving nitrogen use efficiency in tea plant.